Efficacy of dexamethasone for the prevention of nausea and vomiting associated with intrathecal chemotherapy and ketamine sedation in children with leukemia - Chanchai Traivaree (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2010